Religion and the Future of Nigeria: Lessons from the Yoruba Case - J.D.Y. Peel (Yoruba Studies Review)
This paper presents an illuminating analysis of the place of religion in Yoruba social and political life, and why the Yoruba experience represents a great example to the rest of Nigeria, particularly the religiously-volatile north of the country. Combining multiple approaches from historical sociology, the sociology of religlon, political history and the public lives of critical political and religious agents over a period of about a century of Yoruba history, the article explains why the Yoruba case is an exemplar in religious harmony. He argues that the Yoruba are constantly pressed towards olaju (modernity/development/progress) which makes cross-cutting communal belonging more salient, thus ensuring that the Yoruba constantly mobilize both religious and secular institutions and processes in the all-embracing project of olaju.